A Large-Scale Outbreak of Bovine Ephemeral Fever in Turkey, 2012 - Tonbak, Sukru; Berber, Engin; Yoruk, Mustafa Deniz; Azkur, Ahmet Kursat; Pestil, Zuleyha; Bulut, Hakan (Japan Soc Vet Sci, 2013)
Regional cases of bovine ephemeral fever (BEF) were documented previously in Turkey. Previous cases were confirmed in South-East Turkey with low cow mortality. Recent BEF-suspected outbreaks with high mortality were documented in many regions of Turkey in 2012. The aim of study was the epidemiological examination of the outbreak and molecular characterization of the viruses detected from the outbreak. For this reason, blood samples were collected from BEF-suspected outbreak regions. From the results of RT-PCR, high rate of BEF-suspected samples (48/60 or 80%) was found positive for BEF virus (BEFV) RNA. The nucleotide sequences of the G(1) region of G gene of BEFV in the current study during the 2012 outbreak were grouped into cluster II of BEFV. It was suggested that BEFV may be spread out to other neighbor countries in the future years.
Keywords: bovine ephemeral fever; bovine ephemeral fever virus; outbreak; RT-PCR